Promotion of traditional pharmaceutical product: a case study of herbal preparation - Ampah, Isaac Carl (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of the Degree of Master of Arts in Industrial Management.